2017
DOI: 10.5114/ada.2017.67082
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of venom immunotherapy: a real life study

Abstract: IntroductionVenom immunotherapy (VIT) is recommended as the first-line treatment for patients allergic to Hymenoptera venom.AimTo analyze the safety and efficacy of VIT in a real life setting.Material and methodsOne hundred and eighty patients undergoing VIT were studied to evaluate the safety, efficacy, incidence and nature of symptoms after field stings and adverse reactions to VIT.ResultsSignificantly more patients were allergic to wasp than bee venom (146 vs. 34, p < 0.0001). Early and late side effects we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 19 publications
1
27
0
2
Order By: Relevance
“…This finding is consistent with previous studies. 8,9,10 The rapid protocols were safer than the conventional therapy, but these differences were frequently on the boundary of statistical significance. The safety of the rapid protocol has been compared many times since 1980.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with previous studies. 8,9,10 The rapid protocols were safer than the conventional therapy, but these differences were frequently on the boundary of statistical significance. The safety of the rapid protocol has been compared many times since 1980.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were also opposing findings, for example, men are more susceptible to allergic adverse reactions during bee venom VIT. 10 Our observational study focused on one type of vaccine -Venomenhal (Hal Allergy, Leiden, Netherlands). This homogeneity resulted in greater reliability for comparing adverse reactions in patients.…”
Section: Discussionmentioning
confidence: 99%
“…The application of BV generally leads to frequent adverse reactions such as pruritus and edema at the site of application [85]. Although allergy to BV has been described, it is not frequent and the use of an allergy test allows its identification in a timely manner [86,87]. The allergy to propolis, honey, royal jelly, and pollen, although they have been described, are much less frequent [88][89][90].…”
Section: An Integrative Visionmentioning
confidence: 99%
“…In recent studies, objective systemic adverse events (AE) were reported in 2.7 to 17.8% of patients. [1][2][3] It is well known that systemic AEs occur more frequently during the up-dosing phase of bee VIT compared with vespid VIT. 1,4,5 However, the rate of AEs was usually analyzed in mono-venom immunotherapy or in stepwise dual immunotherapy Ninety-two patients were treated with bee venom, 435 with vespid venom, and 123 simultaneously with bee and vespid venom; the rate of systemic AEs was 10.9%, 6.4%, and 10.6%, respectively.…”
Section: Simultaneous Up-dosing Of Bee and Vespid Venom Immunotherapymentioning
confidence: 99%